Advancements in Wound Dressings: The Role of Chitin/Chitosan-based Biocomposites - Salehi, Majid; Mirhaj , Marjan; Banitorfi Hoveizavi, Nadia; Tavakoli , Mohamadreza; Mahheidari, Naimeh (Journal of Composites and Compounds, 2025)
This review explores recent advancements in chitin and chitosan-based biocomposites for wound dressing applications, emphasizing their unique physicochemical properties such as biocompatibility, biodegradability, and antimicrobial activity that underpin their therapeutic efficacy. It discusses their pivotal role in wound healing and evaluates innovative dressing technologies, including antimicrobial, smart, and stimuli-responsive systems. Additionally, the review covers their clinical applications across various wound types, including acute, chronic, and surgical wounds, while emphasizing emerging trends and future directions for integrating these biocomposites into next-generation wound management strategies. The insights provided aim to underscore the potential of chitin/chitosan-based materials in advancing wound care practices.